Levels, methods of application and sources of phosphate on corn production - Vasconcellos, Carlos Alberto; Santos, Hélio L. dos; França, Gonçalo E. de; Bahia Filho, Antônio F. de C.; Pitta, Gilson V. E. (Pesquisa Agropecuaria Brasileira, 2014)
Corn experiments were conducted for five years on a dark red latosol, originally under “cerrado” vegetation, to study levels, application methods and sources of phosphates. The efficiency of superphosphate and Patos de Minas rock phosphate broadcasted on soil surface and incorporated in the first years was compared for five years. In the year with dry period during cropping season more phosphorus was necessary to obtain maximum yield. The relative efficiency of broadcast phosphorus fertilization decreased with successive band application. The first year 39.4 kg P2O5 ha-1 of band application was necessary to produce the equivalent grain yield of 100 kg P2O5 ha-1 as triple superphosphate broadcast. Only 11 kg P2O5 ha-1 was necessary in the row to reach the same 100 kg P2O5 ha-1 band application. The economic fertilization was broadcast 200 kg of total P2O5 ha-1 and 150 kg P2O5 ha-1 in the row annually. Independently of broadcast levels and phosphate source used at 10 cm with 15 cm depth strip increasely 15% over the conventional band application. The critical economical P available by Mehlich I extractant, was 13.8 ppm. The Patos de Minas rock phosphate was an inadequate source for broadcasting fertilization.